They Aren't, Until I Call Them Performing the Subject in American Literature - Bollobás, Enikö (Peter Lang International Academic Publishers, 2010)
In the story of the three baseball umpires, two novice umpires compete in boasting how they respect «truth» and the way things «really» are. One says, «I call them the way I see them»; the other, trying to trump this remark, responds, «I call them the way they are». Then enters the third, most seasoned umpire, saying, «They aren't, until I call them». This book deals with two widely argued issues in literature criticism today, performativity and subjectivity. How do people become who they are? What scripts do they follow when they «do» gender, race, and sexuality? Tying into speech act theories and subjectivity theories, as well as gender, race, and sexuality studies, the author explores - through the close reading of several American texts - the many ways words make «things» in literature.